2011
DOI: 10.2304/ciec.2011.12.1.56
|View full text |Cite
|
Sign up to set email alerts
|

Discourses of the Early Years Learning Framework: Constructing the Early Childhood Professional

Abstract: In Australia, as elsewhere, many factors have contributed to making the struggle for recognition of the professional status of early childhood difficult and ongoing. Arguably this has led to instabilities surrounding professional identity and how members of the field regard themselves and their work. The development and release of the Early Years Learning Framework for Australia (EYLF) was perceived by many as an opportunity to raise the status and standing of the early childhood professional within the early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…While curriculum frameworks have the power to 'lift professional standards to a more sophisticated level' (Nuttall & Edwards, 2007, p. 13) there is no evidence that such documents can make practitioners practice in a more 'professional' manner or identify more strongly as 'educators' (Ortlipp et al, 2011). To achieve such an ideological shift, Ortlipp and colleagues (2011) suggest that the discourse of professionalism needs to be taken up by 'professional' workers themselves.…”
Section: Discussionmentioning
confidence: 99%
“…While curriculum frameworks have the power to 'lift professional standards to a more sophisticated level' (Nuttall & Edwards, 2007, p. 13) there is no evidence that such documents can make practitioners practice in a more 'professional' manner or identify more strongly as 'educators' (Ortlipp et al, 2011). To achieve such an ideological shift, Ortlipp and colleagues (2011) suggest that the discourse of professionalism needs to be taken up by 'professional' workers themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Next, identity in practice always represents an interplay between the local and the global (Wenger, 1998). For instance, Ortlipp, Arthur, and Woodrow (2011) argue that since local practice is informed by regulations, standards, and curriculum documents, changes in these frameworks impact professional identity construction, especially in new educators. Finally, individuals always belong to multiple communities, which may deviate in terms of ways of being and acting.…”
Section: Conceptual Framework: Communities Of Practicementioning
confidence: 99%
“…These documents commonly detail what children are expected to learn and by so doing indicate what teachers must know, how they should teach, and how can they be helped (Alvestad & Duncan, 2006;Ortlipp, Arthur, & Woodrow, 2011;Rockel, 2009;Sofou & Tsafos, 2010). However, studies of national curricula have found these documents can undermine teachers' professional autonomy and generate difficulties for practitioners if these practitioners are expected to gain new knowledge and adapt long-established work practices without the resources required to achieve these goals.…”
Section: The Literaturementioning
confidence: 99%
“…However, studies of national curricula have found these documents can undermine teachers' professional autonomy and generate difficulties for practitioners if these practitioners are expected to gain new knowledge and adapt long-established work practices without the resources required to achieve these goals. Ortlipp et al (2011) argue that the extent to which ECE work is affected by government policies depends on the level of knowledge and skills teachers bring to the process.…”
Section: The Literaturementioning
confidence: 99%